A Review on Some Medicinal Plants with Hepatoprotective Effects - Okaiyeto, Kunle; Nwodo, Uchechukwu U.; Mabinya, Leonard V.; Okoh, Anthony I. (Pharmacognosy Reviews)
Liver diseases have become a major global health challenge and may be triggered by several toxic chemicals, which include chemotherapeutic agents, thioacetamide, carbon tetrachloride, certain antibiotics, excessive alcohol consumption, and pathogenic microbes. Hence, safeguarding a healthy liver is vital for good health and well‑being. Despite advances in pharmacology, the demerits associated with synthetic drugs have outshone the merits. Treatment of liver diseases based on modern medical principles is becoming ineffective and also associated with adverse effects of long‑term use, in addition to prohibitive costs in developing countries. Thus, exploring medicinal plants which are easily available and cheap and do not involve strenuous pharmaceutical production processes appears to have gained worldwide attention as alternative therapeutic agents for the diseases. Consequently, emphasis has been placed on folkloric herbs with high efficacy, low toxicity, and cost‑effectiveness. In this paper, literature search was conducted using various databases such as Google Scholar, ISI Web of Knowledge, and PubMed; we carried out a comprehensive review on existing information on some medicinal plants around the world with hepatoprotective prospects. Phytochemical compounds with hepatoprotective effects were also discussed, and finally, the future work in the field was also highlighted.
Keywords: Bioactive compounds; hepatotoxicity; liver diseases; medicinal plant; pharmacology